MENINGKATKAN KREATIVITAS SISWA KELAS XI SMK NEGERI 4 PADANG DALAM BERKARYA BATIK TULIS - Edali Lase; Desi Trisnawati; Yuniarti Munaf (Institut Seni Indonesia Padangpanjang, 2022)
This study uses a qualitative method which aims to determine the form of student creativity in hand-drawn batik before and after the research, the supporting and inhibiting factors of students' creativity in writing batik, and the form of student creativity in learning batik. The researcher acts as an instrument that goes directly to the field with data collection methods in the form of observation, interviews and documentation. The results of this study indicate that the creativity of students in making written batik before the research did not achieve maximum results in terms of shapes, motifs, colors and attachments and students only used shapes, motifs and colors determined by the teacher based on the tasks according to the Learning Implementation Plan (RPP). due to limited learning time during the covid-19 pandemic. The results of learning batik after research, students' creativity has increased. Students have been able to develop the form of batik work, give birth to their own creative motifs, use various colors and the attachments look neat and unbroken. Efforts are made to increase student creativity, namely; utilizing facilities and infrastructure in the form of theoretical rooms, corridors, chairs and tables as an alternative to the limited practice space and batik equipment and preparing various learning media in the form of pictures, videos of the batik process and batik products that have been produced.